Pengaruh reward terhadap motivasi belajar mahasiswa Tadris Matematika kelas b pada pembelajaran mata kuliah teori bilangan - Hidayati, Siti (Maliki Interdisciplinary Journal, 2023)
Learning is sometimes an unpleasant thing for some people. Therefore, creativity development is needed in updating the learning system so that students can be motivated to follow the lesson properly and correctly. One of these developments is the provision of rewards in the learning process. This article is based on the results of research through questionnaires that have been distributed to third-semester mathematics tadris students in class B regarding the effect of giving rewards on learning motivation.The research was conducted in a closed manner which was devoted to members of class B students of tadris mathematics aimed at seeing how the interest and performance of students in learning number theory,when in learning there is a reward. By using quantitative research methods, it can be seen that most of the third semester mathematics students of class B like the provision of rewards during number theory lesson.In addition to increasing student interest and performance, giving rewards at the time of learning is also considered interesting so that students' enthusiasm in carrying out number theory lessons is also considered.